Cystic Fibrosis Facts, Management and Advances - Mohite, Prashant; Reed, Anna; Simon, André R. (IntechOpen, 2021)
Cystic fibrosis, a genetic disorder in children and young adults, is a multisystemic disease that mainly affects the lungs. Advances and improvements in the diagnosis and management of this condition have led to increased overall and symptom-free survival in cystic fibrosis patients. This book examines recent advances in the field and presents an evidence-based approach to the management of cystic fibrosis.